The Influence of Coal Gangue Particle Size on Water Retention Characteristics - Lei Zhu; Xinfu Zhang; Jiahui Li; Mei Wang; Zhicheng Liu; Mingli Geng; Lang Liu; Ruofan Wang (Advances in Civil Engineering)
This study systematically studied the moisture characteristic curves, water-holding capacity, and infiltration performance of different particle sizes of gangue in Nanliang coal mine and Dahaize coal mine by comprehensively using numerical simulation and measured data. The HYDRUS model was used to fit the measured moisture characteristic curve, determine the relevant soil parameters, and perform numerical simulations through the set boundary conditions to verify the reliability of the model. The results show that as the particle size of the gangue increases, the saturated water content gradually decreases, and the gangue with a smaller particle size exhibits a superior water-holding capacity. In terms of wetting front migration, the migration distance of gangue with different particle sizes changes with time in a power function relationship, and the migration speed of gangue with a particle size of 1.25–2.5 mm is the fastest. Infiltration experiments show that gangue with a smaller particle size has a higher infiltration rate and a longer saturation time. The influence of coal gangue particle size on the water retention capacity and permeability of coal gangue is greater than the influence of coal gangue type on the water retention capacity and permeability of coal gangue. The gangue of Nanliang coal mine shows significant advantages in moisture characteristics, and its water-holding capacity and infiltration performance are significantly better than those of Dahaize coal mine. This study systematically quantified the effects of different particle sizes of coal gangue on soil water retention characteristics, providing a new theoretical basis for its application in soil improvement. By combining numerical simulation and measured data verification methods, the accuracy and reliability of the research results were improved, providing an important reference for similar studies in the future. In addition, the significant effects of coal gangue particle size on soil wetting front migration speed and profile water content were revealed, providing new insights and basis for optimizing water resource management strategies.